Recovery of Reactive (Triazine) Dyes from Textile Effluent by Solvent Extraction Process - TUTEJA*, RAVINDER; KAUSHIK, NAMRATA; KAUSHIK, C.P.; SHARMA, J.K. (Asian Journal of Chemistry, 2024)
In the present work, triazine reactive dyes are recovered from the textile effluent by the solvent extraction process using surfactants. Work is carried out on three different triazine dyes i.e., reactive blue 171, reactive red 141 and reactive yellow 84. As these dyes are anionic in nature so cationic surfactant i.e., hexadecyl trimethyl ammonium bromide (HTAB) is used for the forward extraction of dye into solvent phase. For the backward extraction of dye into aqueous phase an anionic surfactant is used to counter the charge effect i.e., sodium dodecyl benzene sulfonate (SDBS). The cationic surfactant is chosen in such a way that it forms reverse micelle with solvent. Isoamyl alcohol is selected as solvent for the present studies, since the other lower alcohols are soluble in water, where as it is almost immiscible and forms distinct upper layer in aqueous solution. The effects of different parameters, such as the surfactant concentration, pH and electrolyte (NaCl) concentration are studied in the present work.